Post Operative Functional Outcome of Modified Tension Band Wiring in Patients with Transverse Fracture of Patella (Journal of Fatima Jinnah Medical University, 2018)
Aims and Objectives: To determine the post operative functional outcome in patients with transverse fracture of patella managed with modified tension band wiring. Study Design: It was a prospective descriptive randomized control trial study. Duration: From 01st July 2009 to 31st September 2010. Material and Method: 45 patients with displaced transverse fracture of patella, treated by modified tension band wiring were studied with rehabilitation program to determine the functional outcome, according to Goodfellow grading. Study was carried out in the department of Orthopaedic & General Surgery, Fauji Foundation Hospital (FFH), Rawalpindi. Result: Total of 45 patients were included in study, age ranges between 20 years to 67 years. 38(84.45%) 38(84.45) were male and 07(15.55%) 7 (15.55) were female patients. Right knee was involved in 29 cases (64.44) (64.44%) where as left knee was involved in 16(33.33%). There was gradual increase in Goodfellow grading in each follow up and more than 70% of the patients had a good Good, fellow grade after 03 month. months of I.F. However female patients had a slow recovery as compare to male patients. Regarding the range of motion 39 ( 87%) patients had a range of motion more than 90 degrees at the end of three months period, which can be regarded as acceptable function of knee. Conclusion: Following the post operative rehabilitation program properly followed after modified tension band wiring in transverse fractures of patella, good functional outcome can be achievedwithin 3 months of fixation.
Keywords: Fracture patella, Goodfellow grading